Volume 9: 40th Computers and Information in Engineering Conference (CIE) 2020
DOI: 10.1115/detc2020-22582
|View full text |Cite
|
Sign up to set email alerts
|

Is Verifying Frequently an Optimal Strategy? A Belief-Based Model of Verification

Abstract: Verification activities increase an engineering team’s confidence in its system design meeting system requirements, which in turn are derived from stakeholder needs. Conventional wisdom suggests that the system design should be verified frequently to minimize the cost of rework as the system design matures. However, this strategy is based more on experience of engineers than on a theoretical foundation. In this paper, we develop a belief-based model of verification of system design, using a single system requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…The results presented in Section 4.1 generalize our previous work 42 . In this section, we explicitly define the effect of εn,l and N on frequent verification being an optimal strategy.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The results presented in Section 4.1 generalize our previous work 42 . In this section, we explicitly define the effect of εn,l and N on frequent verification being an optimal strategy.…”
Section: Discussionsupporting
confidence: 68%
“…The model and results in this paper expand our previous work, 42 where we used a belief‐based model to determine the optimal verification strategy for a single organization focused on a single system requirement, or the requirement of interest. In that work, 42 we showed that frequent verification was not, in general, an optimal verification strategy. However, the belief‐based model used in that paper assumed that the organization's confidence in its design activities not resulting in an error in the system design was constant throughout the design process.…”
Section: Background and Motivationmentioning
confidence: 62%
See 1 more Smart Citation
“…Yet, majority of the literature on verification activities adopts the aleatory uncertainty approach 3,5,21–37 . The reader is referred to ref 38,39 . for a discussion on these works and the drawbacks of adopting the aleatory uncertainty approach to model systems engineering projects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent works on verification in systems engineering have begun to explore the benefits of modeling the epistemic uncertainty in systems engineering projects with belief distributions 38–47 . In these works, belief distributions are used to model the subjective confidence of designers in the true state of the system design.…”
Section: Introductionmentioning
confidence: 99%